Development and preliminary testing of a bambara groundnut sheller - Alonge, Akindele Folarin; Bassey, E.; Esua, Okon Johnson; Chikwendu, Onwude Daniel Iroemeha (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
A centrifugal bambara groundnut pod shelling machine was designed and constructed to crack various sizes and varieties of bambara groundnut. The sheller was fabricated with locally available materials from the formation of a new idea which aimed at easing the pain, stress, intensive labour, time consumption, undue cost and the cumbersome operation encountered in the traditional method of shelling. The machine consists of three main units, namely the hopper, shelling unit and power transmission unit. The sheller uses impact technique and was designed to shell bambara groundnuts effectively and also to eliminate drudgery associated with the traditional methods of shelling legumes. Five hundred (500) samples of sundried bambara groundnuts at 6% (wet basis) which were randomly selected were shelled at an impeller rotation speed of 1636 rpm. The results of the test showed that the shelling efficiency, seed damage, partially shelled pods, unshelled pods and the machine capacity were 83.2%, 17.4%, 7.8%, 9% and 75000 seeds/hr respectively.